Agripreneurship Nurul Hayat Malang Branch Risk Management - Nabilah Zhafirah; Rahayu Relawati; Bambang Yudi Ariadi (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2021)
Since 2003, Nurul Hayat's company has been involved in agrienterprise, particularly in collaboration with goat farmers in the establishment of aqiqah services. Nurul Hayat's agrienterpreneurship activities have grown throughout Indonesia, with over 30 branches. Nurul Hayat's commercial activities have been impacted by the covid-19 epidemic since the beginning of 2020, with a decline in bookings in practically all branches. The purpose of this study is to determine the hazards associated with the Nurul Hayat Malang branch's agribusiness activities. Risk management is the application of management functions to address the company's hazards. This study uses house of risk phase 1 methodology and analytical tools. Primary data from consumers and the brand manager of the Malang branch, Nurul Hayat. According to experts from brand managers, there are 11 risk events and 8 risk agents encountered by agrienterpreneurship Nurul Hayat Malang branch. Second, risk agent has the potential to arise because it is included in 80 percent of the cumulative ARP (aggregate risk potential), where this occurs due to the failure of the Nurul Hayat Malang branch of agrienterpreneurship to reach the target (A3) and quality and product standards (A6). Nurul Hayat agrienterpreneurship partner malang branch should be expanded, and the quality control team should be evaluated, according to the recommendations.